Implementasi Project Based Learning dalam Membangun Keaktifan Mahasiswa - Rotari, Septi (ASANKA : Journal of Social Science and Education, 2023)
ABSTRACTThis article is entitled Implementation of Project Based Learning in Building Student Activeness, the purpose of writing is to describe the project model in learning as an effort to build student activeness. Through a literature review, we examine Project Based Learning as a learning model so that students can have the ability to understand, read actively, be able to analyze, be able to think critically, and be able to find or create results from the material they have studied. Through Project Based Learning, students will be more active and can use higher level thinking skills, so that student activity can be directly formed well.Artikel ini berjudul Implementasi Project Based Learning Dalam Membangun Keaktifan Mahasiswa, adapun tujuan penulisan adalah untuk mendeskripsikan model proyek dalam pembelajaran sebagai upaya membangun keaktifan mahasiswa.  Melalui kajian pustaka dikaji tentang Project Based Learning sebagai model pembelajaran agar mahasiswa dapat memiliki kemampuan memahami, bersikap aktif, dapat menganalisis, dapat berpikir kritis, serta dapat menemukan atau menciptakan hasil dari materi yang telah dipelajari. Melalui Project Based Learning mahasiswa akan lebih aktif serta dapat menggunakan kemampaun berpikir tingkat tinggi, sehingga secara langsung keaktifan mahasiswa dapat terbentuk dengan baik.